Guano Dan Pupuk Organik Cair Bagi Masyarakat Desa Olibu - safriyanto Dako; Netty Ino Ischak (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
AbstractThe purpose of this service is to provide knowledge and competence for the Bat Utilization Group in the manufacture of liquid organic fertilizer made from bat guano. This activity has been carried out in Olibu Village, Gorontalo Province. The implementation method is through PRA and field practice. The partner group is the Bat Utilization Group. The application of knowledge and competence on the manufacture of liquid organic fertilizer resulted in an increase in group knowledge and competence. As many as 78.95% of group members do not know the benefits of guano or dried bat droppings, while as many as 21.05% of members know information from other people, but have never done it. At the end of the activity, a final test was conducted on the group and all members. There was an increase in the knowledge and skills of group members in making POC by 63.16%. Application of POC Making helps Bat Utilization Groups to improve their knowledge and skills. The added value obtained is that the contribution of organic fertilizer to agricultural land can be done alone Keywords: Bat Utilization Group, Bat Conservation, Liquid Organic Fertilizer (POC), Knowledge